Tailoring the Molecular Properties with Isomerism Effect of AIEgens. (15th July 2019) - Chen, Ming; Liu, Junkai; Liu, Feng; Nie, Han; Zeng, Jiajie; Lin, Gengwei; Qin, Anjun; Tu, Mei; He, Zikai; Sung, Herman H. Y.; Williams, Ian D.; Lam, Jacky W. Y.; et al.
Abstract: It is challenging to achieve precise control on the properties of organic π‐functional materials to widen their practical applications. On the other hand, the study of aggregation‐induced emission luminogens (AIEgens) helps achieve such goals because of inherent relationships between their luminescence behaviors and conformational variations that allow for the visual monitoring of the changes in the material properties. Inspired by this, in this work, three AIE isomers are fabricated in structures consisting of tetraphenylpyrazine and triphenylethene units with para ‐, meta ‐, and ortho ‐position linkages, respectively. The isomerism effect brings about significantly decreased luminescence efficiency, subtly blueshifted emission, basically reduced AIE effect but boosted porosity in the aggregate state as the conformation of AIEgens evolves from an extended to a folded one. Based on the distinct properties, their respective use in blue organic light‐emitting diodes, nanofluorescent probes, and molecule‐capturing porous crystals are investigated. This work not only achieves precise property control by using the isomerism effect of AIEgens but also provides useful information on the future design of π‐conjugated materials with advanced functionalities. Abstract : Precise control on the properties of π‐conjugated functional materials is a hot topic in the fields of photoelectronics, energy, and catalysis. This work achieves remarkable success with this target by reading the molecular information of isomeric AIEgens, thus providing useful information for designing materials with defined functionalities.